Religious Traditions and Cultural Integration: Pathways to Harmonization and the Promotion of Moderation in Contemporary Muslim Societies - Dedi Supriadi; Anwar Sanusi; Reslawati Reslawati; Dede Burhanudin; Masmedia Pinem (Journal of Islamic Thought and Civilization, 2026)
To encourage harmony and moderation in modern Muslim countries, this study aimed to investigate how religious traditions support cultural integration. The main research questions looked into how Muslim communities' religious traditions support cultural integration and how they can encourage religious moderation in the face of modernity's problems. Using a case study methodology and a qualitative research design, the study examined Muslim communities in culturally diverse nations, such as Indonesia and Malaysia. The primary data sources were derived from direct observation of Muslim communities in culturally diverse countries, such as Indonesia and Malaysia. A purposive sampling method was used to select Muslim communities with significant cultural diversity. Data analysis was conducted through thematic analysis procedures to identify patterns of interaction between local cultural aspects and religious traditions. The study's main conclusions showed that religious customs can significantly improve social cohesiveness and reduce conflict likelihood when modified to reflect local cultural norms. Through an inclusive framework that prioritizes universal Islamic values, for instance justice, tolerance, and human dignity, these traditions serve as vital tools for advancing religious moderation. By combining sociological and theological viewpoints, this study added to the body of knowledge by thoroughly examining the relationship between religious and cultural dynamics. To promote moderation in Muslim countries, the study also suggested a paradigm for the culturally sensitive application of religious customs.